DIGITIZING NOTARIAL PROTOCOLS: A COMPARATIVE STUDY OF INDONESIA, NETHERLANDS, AND GERMANY - Dio Ahmad Hafidzan; Isis Ikhwansyah; Nanda Anisa Lubis (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This study aims to analyze the legal framework governing the digitization of notarial protocols in Indonesia and to identify reform strategies through a comparative legal approach. The research objects comprise the regulatory systems of Indonesia, the Netherlands, and Germany, three civil law nations at different stages of digital transformation in notarial practice. Using a normative juridical method with a comparative statute and conceptual approach, this study examines primary legal sources including legislation, government regulations, and notarial association guidelines from each jurisdiction. The findings reveal that the Netherlands and Germany have established comprehensive legal frameworks for digital notarial protocols, ensuring authenticity, integrity, and long term legal certainty through electronic archiving systems and digital signature regulations. In contrast, Indonesia's existing legal instruments remain fragmented and inadequate to fully support the digitization of notarial protocols. This study concludes that Indonesia urgently requires a systematic legislative reform, drawing upon best practices from the Netherlands and Germany, to achieve legal certainty in notarial documentation within the era of digital transformation.